2012
DOI: 10.1093/tropej/fms043
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Neonatal Mortality in Jhagadia Block, Gujarat: We Need to go Beyond Promoting Hospital Deliveries

Abstract: Although community based interventions along with promotion of hospital birth has an impact in reducing neonatal deaths in this community, sustaining this momentum may demand more long-term policy interventions to promote better living standards and better reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…After collecting baseline information for 2 years from 1 April 2002 to 30 March 2004, SEWA Rural implemented a family‐centred safe‐motherhood and new‐born survival project for 7 years from 1 April 2004 to 31 March 2011 which catered to the entire Jhagadia block consisting of 168 villages with a population of 175 000, which is mainly tribal, rural and poor (SEWA Rural ; Kutty et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…After collecting baseline information for 2 years from 1 April 2002 to 30 March 2004, SEWA Rural implemented a family‐centred safe‐motherhood and new‐born survival project for 7 years from 1 April 2004 to 31 March 2011 which catered to the entire Jhagadia block consisting of 168 villages with a population of 175 000, which is mainly tribal, rural and poor (SEWA Rural ; Kutty et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…This study is based on prospectively collected communitybased data by field-based front-line workers ( Kutty et al 2013).…”
Section: Study Settingmentioning
confidence: 99%
“…In a cohort of births examined in Gujarat, it was concluded that for sustaining the momentum of reduced neonatal mortality there is a need of long-term policy intervention to promote better living standards and better reproductive health. 57 Racial and Ethnic Approaches to Community Health (REACH) is an initiative promoted by the Centers for Disease Control and Prevention's (CDC), which strives to eliminate racial and ethnic disparities in health. It is a communitybased, participatory approach to identify, develop and disseminate effective strategies for addressing health disparities across a wide range of health priority areas such as cardiovascular disease, diabetes, breast and cervical cancer, infant mortality, asthma, immunization, and obesity.…”
Section: Administrative Reforms Approachmentioning
confidence: 99%
“…Globally it has been estimated that there were 5.2 million under-5 years childhood deaths in 2019 1 of which 20% occurred in India. 2 In India in 2004, the mortality rates/1000 live births were U5MR (number of deaths…”
Section: Introductionmentioning
confidence: 99%